2016
DOI: 10.1002/bkcs.11022
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Applications of Force Spectroscopy Using Atomic Force Microscopy

Abstract: Single‐molecule force spectroscopy is a powerful technique for addressing single molecules. Unseen structures and dynamics of molecules have been elucidated using force spectroscopy. Atomic force microscope (AFM)‐based force spectroscopy studies have provided picoNewton force resolution, subnanometer spatial resolution, stiffness of substrates, elasticity of polymers, and thermodynamics and kinetics of single‐molecular interactions. In addition, AFM has enabled mapping the distribution of individual molecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 152 publications
0
11
0
Order By: Relevance
“…Information obtained by SMFS is significant for understanding of the relations between molecular structure and functions of various substances . SMFS is used for determination of very small forces in a range of pN, provides information about sample topography, their mechanical properties and is useful for study the thermodynamics and kinetics of molecular interactions . SMFS is excellent tool for direct measurements of intermolecular bonds, for obtaining information on infrequent molecular states and on mechanical properties of molecules that are important for protein functions .…”
Section: Resultsmentioning
confidence: 99%
“…Information obtained by SMFS is significant for understanding of the relations between molecular structure and functions of various substances . SMFS is used for determination of very small forces in a range of pN, provides information about sample topography, their mechanical properties and is useful for study the thermodynamics and kinetics of molecular interactions . SMFS is excellent tool for direct measurements of intermolecular bonds, for obtaining information on infrequent molecular states and on mechanical properties of molecules that are important for protein functions .…”
Section: Resultsmentioning
confidence: 99%
“…The intra- and intermolecular interactions of the polymer are obtained directly through the stretching of the polymer bridge by the AFM tip in different surrounding environments. A detailed review of AFM in terms of the fundamentals of force spectroscopy, sample preparation, data analysis and applications, and its future, is presented by Park and his coworkers [ 23 ]. Gaub et al found that the elongation of the polymer chains was governed by the distortion of the bond angles at higher forces through SMFS.…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we report a direct approach to detect KRAS G12D mutation in ctDNA samples extracted from patients’ plasma with very low mutant allele frequencies (0.006–0.2%) at high sensitivity/specificity (near 100%) by force–distance (F-D) curve-based AFM. The remarkable specificity of MutS protein, which binds to only the mismatched DNA duplexes in lieu of fully matched ones, was utilized to sense only the mutated genes. A specifically designed LNA/DNA chimeric blocker was placed into the ctDNA sample solution prior to the denaturation step to make the desired target sequence accessible to the capture probe.…”
mentioning
confidence: 99%